A parametric study on the optimization of a metamaterial-based energy harvester. (12th October 2015) - Li, Kaiyuan; Rizzo, Piervincenzo; Bagheri, Abdollah
Abstract: Highly nonlinear solitary waves (HNSWs) are compact nondispersive waves that propagate in nonlinear medium such as straight chains of spherical particles. In the last two decades, these waves have found many applications in physics and engineering including lensing and nondestructive testing. In the study presented in this paper, we exploit the propagation of HNSWs along a metamaterial formed by granular chains to harvest energy from an oscillating structure. Specifically, an oscillator taps the metamaterial and creates a train of solitary waves along each chain. At the interface between the chains and a solid material, part of the acoustic energy refracts into the solid where it coalesces at a point. Here, a wafer-type transducer converts the focalized stress wave into electric potential. In the research presented in this study, we optimize some of the harvester's parameters to maximize the electrical power output. The results demonstrate that the proper selection of parameters such as beads' material and size, speed of the oscillator at the instant of the impact, and modulus of the solid increases, by several orders of magnitude, the amount of power that can be harvested.